Novel ascorbic acid sensor prepared from gold/aniline-pentamer-based electroactive polyamide composites - M-H. Tsai; S. H. Lu; Y. H. Lai; G-H. Lai; G. V. Dizon; T-I Yang; Y-J. Lin; Y. C. Chou (eXPRESS Polymer Letters)
A novel gold/aniline-pentamer-based electroactive polyamide (Au/EPA) composites that can modify carbon paste electrodes (CPEs) for ascorbic acid (AA) sensing has been studied in detail in this article. Cyclic voltammetry studies indicated improved electrochemical properties of the Au/EPA composites, demonstrating the occurrence of efficient electron/charge transfer between the Au and the EPA. Experimental tests shows that there is a linear relationship between the concentration of added AA and the response current for the CPE modified with Au/EPA sensor to the concentration of AA in the range of 0.05–0.75 mM (R2 = 0.996, n = 15). The detection limit and the sensitivity of the Au/EPA-CPE AA sensors were 2.75 µM at a signal to noise ratio (S/N) of 3, and 21.7 mA·mM–1, respectively.